Shorter disease duration in females with sporadic frontotemporal dementia. (20th December 2022) - de Boer, Sterre C.M.; Riedl, Lina; Van der lee, Sven J; Otto, Markus; Anderl‐Straub, Sarah; Landin‐Romero, Ramon; Sorrentino, Federica; Fieldhouse, Jay L.P.; Reus, Lianne M.; Halliday, Glenda M; Galimberti, Daniela; Diehl‐Schmid, Janine; et al.
Abstract: Background: Previous reported sex differences on disease duration (DD) of frontotemporal dementia (FTD) have been inconsistent and lack the comparison between genetic and sporadic FTD. Our aim was to study the difference in disease duration between males and females in genetic and sporadic FTD. Method: Mortality data was obtained from 61 deceased patients with genetic FTD (52% male) and 117 deceased patients with sporadic FTD (64% male) from the international FTD cohort previously reported by de Boer et al., 2021. The age at symptom onset (AAO), age at death (AAD) and the DD (defined as the time between age at symptom onset and age at death) were compared between males and females in the genetic and sporadic FTD group using Mann Whitney U tests. Result: Genetic FTD did not show significant sex differences in AAO, AAD and DD (p = 0.3, p = 0.3, p = 0.8 respectively, Figure 1). In sporadic FTD, the AAO and AAD did not significantly differ between males and females (p = 0.8 and p = 0.2 respectively). The DD in the sporadic FTD group was significantly shorter in females (median DD 7.0 years) in comparison to males (median DD 8.0 years, p = 0.01, Figure 2). Conclusion: In this study we show that females with sporadic FTD have a shorter disease duration than males whereas in genetic FTD the disease duration does not differ between sex. These findings suggest the existence of sex‐related differences in the disease course of sporadic FTD. We urge the need for international epidemiological FTD studies to further explore the role of sex in both genetic and sporadic FTD.